Análise da qualidade de resultados GPS em programas comerciais - Moraes, Alarico Valls de (2005)
The Brazilian technician-scientific community that dedicates to the surveying is living a new time with the normatization of the technical parameters for reference of the geodesic surveys to Cadastro Nacional de Imóveis Rurais according to Brazilian Law 10.267/2001. The objective of this work is to analyse by means of the statistical parameters the quality of the survey data with GPS-receivers and post-processed in the softwares present in the market. Amongst the analysed parameters, the most important is the standard deviation of the coordinates, because it is the measure for the precision and it is an composition element of the accuracy, that indicate the result quality. The results presented by commercial softwares are compared with the official data of the State Landmark GPS network that are information supplied for the Instituto Brasileiro de Geografia e Estatística (IBGE). Also this work contribute for the relation user-manufacturer approaching them thus first when manipulating the programs get greater information availability how much to the applied methodology to give the processing results. By means of the fundamental univariate and multivariate Statistic concepts, this work give an analysis of as the commercial softwares are processing GPS data and also inform which the necessary minimum data that the softwares must supply to the user in order to give the estimated statistical parameters that are an indication the quality of each geodetic survey.